The uPA System Differentially Alters Fibroblast Fate and Profibrotic Ability in Skin Fibrosis - Zou, Ming-Li; Teng, Ying-Ying; Chen, Zhong-hua; Liu, Si-Yu; Jia, Yuan; Zhang, Kai-Wen; Wu, Jun-Jie; Yuan, Zheng-Dong; Tang, Xiao-Yu; Yu, Shun; Ye, Jun-Xing; Li, Xia; et al. (Frontiers in Immunology, 2022)
Skin fibrosis is a common pathological feature of various diseases, and few treatment strategies are available because of the molecular pathogenesis is poorly understood. The urokinase-type plasminogen activator (uPA) system is the major serine protease system, and its components uPA, urokinase plasminogen activator receptor (uPAR) and plasminogen activator inhibitor-1(PAI-1) are widely upregulated in fibrotic diseases, including hypertrophic scars, keloids, and scleroderma. Here, we found that the successful binding of uPA and uPAR activates the downstream peroxisome proliferator-activated receptor (PPAR) signalling pathway to reduce the proliferation, migration, and contraction of disease-derived fibroblasts, contributing to the alleviation of skin fibrosis. However, increased or robust upregulation of the inhibitor PAI-1 inhibits these effects, suggesting of the involvement of PAI-1 in skin fibrosis. Subsequent in vivo studies showed that uPAR inhibitors increased skin fibrosis in mouse models, while uPA agonists and PAI-1 inhibitors reversed these effects. Our findings demonstrate a novel role for the uPA system and highlights its relationships with skin fibrosis, thereby suggesting new therapeutic approaches targeting the uPA system.